2013
DOI: 10.1590/s1516-14392013005000094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the heat curing on strength development of self-compacting mortars containing calcined silt of dams and Ground Brick Waste

Abstract: The strength development of self-compacting mortars (SCM) containing calcined silt (CS) and ground brick waste (GWB) was investigated. The variables are the nature of addition (CS and GWB) in the binder and the heat curing at different temperatures (20 °C and 60 °C) at 7 and 14 days of curing. Two temperatures 20 and 60 °C were applied to samples with intermediate levels (depending on the drying method applied to precast) for 18 hours in total. In this study, a Portland cement (CEMII), Calcined silt (750 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…[8][9][10][11][12][13][14] P. B. Cachim 15 reported that crushed bricks could be used as a partial replacement for natural coarse aggregate without a reduction in concrete properties for a 15 % replacement ratio; however, a reduction up to 20 % has been noted for a 30 % replacement ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] P. B. Cachim 15 reported that crushed bricks could be used as a partial replacement for natural coarse aggregate without a reduction in concrete properties for a 15 % replacement ratio; however, a reduction up to 20 % has been noted for a 30 % replacement ratio.…”
Section: Introductionmentioning
confidence: 99%
“…For flexural strength of mortars having undergone heat treatment, continuous improvement was observed compared to mortars up to 14 days without treatment, or it was found the opposite effect, this can be explained by the fragility of specimens from this age processing and ripening (Figure 5), it has been proven in the work of Safi et al, (2013). The temperature has a beneficial effect on the resistance of mortars.…”
Section: Scm(cps) Without Treatment Scm(cps) With Treatmentmentioning
confidence: 88%
“…Keeping in view the most important issues in today's construction world is the ability to make concrete with good spread ability in congested or remote areas and also not able to cure concrete during the most important initial hydration stage. It is felt that there is an urgency to develop concrete that can hydrate in itself without external source of water and can perform well in the fresh and hardened state 9–12 . As concrete structures have evolved into more complex ones over the decades, the amount of reinforcement utilized has considerably gone up.…”
Section: Introductionmentioning
confidence: 99%
“…It is felt that there is an urgency to develop concrete that can hydrate in itself without external source of water and can perform well in the fresh and hardened state. [9][10][11][12] As concrete structures have evolved into more complex ones over the decades, the amount of reinforcement utilized has considerably gone up. This has reduced the space between adjacent reinforcement bars making them more congested.…”
Section: Introductionmentioning
confidence: 99%